Spór o regale bartne w ziemi wiskiej w latach 1502-1519 - Herod, Patrycja Ewa (Saeculum Christianum. Pismo Historyczne, 2020)
The article describes, on the basis of preserved documentary sources, the reasons for, and the course and resolution of the dispute about beekeeping regalia in the Wizna Land, which lasted in 1502-19, and ended only thanks to the intervention of the Polish king Sigismund I. First, the dispute between the nobility of Wizna and the beekeepers (1502-11) is discussed, and then the one between the aforementioned nobility and the Mazovian dukes (1512-19). At the same time, the only princely statute devoted to the beekeeping monopoly, which was promulgated by prince Janusz I the Elder on 24 April 1401 in Warsaw, receives an in-depth analysis. The whole article is concluded with a presentation of research results.